Heidegger's phenomenology of perception an introduction. - Kleinberg-Levin, David Michael, 1939- (New Heidegger research., 2020)
This important new book offers an introduction to Heidegger's phenomenology of perception, interpreting and explaining five key words, 'Sein', 'Dasein', 'Ereignis', 'Lichtung', and 'Geschick'. David Kleinberg-Levin argues that, besides preparing the ground for a major critique of metaphysics and the Western world, Heidegger's phenomenology of perception lays the groundwork for understanding perception--in particular, seeing and hearing, as capacities the historical character of which is capable of overcoming and significantly ameliorating the most menacing, most devastating features of the Western world that Heidegger subjected to critique. He proposes that the development of these capacities is not only a question of learning certain skills, but also a question of learning new character and that Heidegger's critique of the Western world suggests ways in which we might learn and develop new, more sensitive, poetic and mindful ways of relating to the perceived world